How Do Large Corporate Power and Oligarchy Contribute to Worsening Income Inequality In Indonesia? - Harsono, Janice Elysia (Winter Journal: IMWI Student Research Journal, 2025)
Indonesia’s rapid economic growth has been accompanied by deepening income inequality driven by corporate dominance and political oligarchy. This study qualitatively analyzed secondary data from government reports, academic literature, and media sources published between 2014–2024. Findings show that 0.02% of Indonesia’s population controls more than half of the nation’s capital, while the average savings of lower-income groups dropped from IDR 3.4 million in 2017 to IDR 1.9 million in 2024. Large corporations, particularly in extractive and palm oil sectors, contribute to inequality through tax avoidance, profit shifting, and exploitation of legal loopholes, often with government incentives despite environmental and social harm. Oligarchic networks further entrench inequality as wealthy elites occupy political positions, influencing policies and regulatory decisions. The middle class has weakened, with over nine million Indonesians slipping into lower-income categories due to rising living costs, stagnant wages, and limited access to essential services. Although tax reforms have targeted high-income groups, the burden still disproportionately falls on ordinary workers, while corporations continue to evade fair taxation. The study concludes that structural reforms in taxation, corporate regulation, and governance transparency are essential to reduce wealth concentration and create a more inclusive, equitable economic system.